Contracts, incentives and organizations: Hart and Holmström Nobel Laureates. Issue 4 (2nd October 2017) - Smirnov, Vladimir; Wait, Andrew
ABSTRACT: This article reviews the contribution of Hart and Holmström, the 2016 Nobel Laureates in economics. Holmström's work on the principal-agent problem answered questions as to what should (and should not) be included in an incentive contract. His work helped explain the simple structure of incentive contracts we typically observe in the real world. The models he developed have been used to address questions of CEO compensation, organizational design and optimal regulation. A key element of Hart's research focused on the question of what are the optimal boundaries of a firm (and indeed, what a firm actually is). In doing so he developed the incomplete-contracts framework, which has subsequently been used to explain many economic phenomena whenever renegotiation is important, including authority and decision-making structures in firms, why financial contracts look the way they do, and various questions in international trade and public policy.